Colonização do xilema de eucalipto por Ceratocystis spp. isolado de diferentes hospedeiros - Firmino, Ana Carolina [UNESP]; Tanaka, Francisco André Ossamu; Silva, Stela Dalva Vieira Midlej; Ito, Margarida Fumiko; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2015)
Ceratocystis sp. is a fungus that colonizes the xylem and acts as the causal agent of wilt and drought in several woody plants. The present study aimed to monitor the colonization of this fungus on the surface of eucalyptus plants (Eucalyptus sp.). Five Ceratocystis isolates from different hosts (eucalyptus, cocoa, mango, teak and atemoya) were used. Thus, eucalyptus plants (clone 219) had part of their vascular system exposed. A suspension containing 106 spores was deposited onto this region. As a control treatment, one plant was inoculated only with autoclaved distilled water. After inoculation, those plants were kept in a humid chamber at 25oC in the dark. Part of the inoculated area was collected at predetermined time intervals (6, 12 and 24 hours) and fixed in “Karnowsky” solution. The samples were prepared and analyzed undera scanning electron microscope. All isolates were capable of germinating, penetrating and developing in the vessel elements of eucalyptus plants within 6 hours. The cocoa isolate apparently had the slowest development within the studied periods. Germination of ascospores, chlamydospores and conidia of cylindrical type could be observed in this period. Twelve hours after inoculation, the amount of mycelium increased in all tested isolates. In cases of mango and eucalyptus isolates, formation of new chlamydospores could be observed. Twenty-four hours after inoculation, except for cocoa isolates, all other isolates already exhibited formation of cylindrical conidiophores. This study demonstrates that these fungal isolates, even from other hosts, are capable of developing in the xylem of eucalyptus plants.
Colonization of eucalyptus xylem by Ceratocystis spp. isolated from different hosts
Keywords: Development; Pathogenicity; Vessel